PENGARUH KETIMPANGAN PENDAPATAN DAN PERTUMBUHAN EKSPOR TERHADAP EMISI CO2 DI INDONESIA - Ulfa, Nadia; Ichsan, Ichsan (LPPM UNIMAL, 2024)
This research aims to determine the effect of income inequality, and export growth on CO2 Emissions in Indonesia. This research uses secondary data from 1990-2021 obtained from the World Bank. The data analysis model uses a Autoregressive Distributed Lag (ARDL) analysis. The research results show that in the short term income inequality has a negative and significant effect on CO2 Emissions in Indonesia, while in the long term income inequality has a positive and insignificant effect on Indonesia's CO2 Emissions. Export growth in the short term has a positive and significant effect on Indonesia's CO2 emissions, while in the long term export growth has a positive and insignificant effect on CO2 emissions in Indonesia.